ADDRESSING ADVERSE CHILDHOOD EXPERIENCES (ACES) BY COMBINING PUBLIC HEALTH, SOCIAL PEDIATRIC AND RICHER COMMUNITY BASED APPROACHES. (18th May 2018) - Loock, Christine; Beaulieu, Emile; Carwana, Matthew; Singh, Tanjot; Hanson, Denise; Suleman, Shazeen
Abstract: BACKGROUND: The Canadian Social Pediatric Interest Group has developed emerging research partnerships over the past decade. In this multi-centre partnership, we characterize social paediatrics programs (SPPs) in three dimensions: 1) fostering health equity; 2) inter-professional integration, and 3) community embeddedness, all of which involve independently complex sets of interventions. The aim of the RICHER (responsive, interdisciplinary, community health, education and research) SPP is to provide timely access to prevention and intervention services for children and youth at higher risk due to multiple social determinants of health(SDoH) including adverse childhood experiences (ACEs) and material and social poverty. OBJECTIVES: Our objectives are to 1) translate SPP knowledge and experience into policy and practice through formal literature reviews and mixed methods research, 2) further develop and integrate SPPs quality improvement(QI) and research, and 3) integrate trauma informed ACE research findings into primary care and paediatric practices in Canada. DESIGN/METHODS: Following established realist synthesis methodology, built on earlier mixed methods research, a literature review was undertaken to identify key mechanisms linking context/environment to health outcomes. The study method included: (1) identifying the review question, (2) formulating the initial theory, (3) searching for primary studies, (4) selecting and appraising study quality, (5) extracting, analyzing and synthesizing relevant data, and (6) refining the theory. Using mixed methods approaches, the RICHER SPP research data was analyzed to identify outcomes, develop and update logic models. Health professional survey of paediatric specialists and surgeons has been developed to explore knowledge of ACEs and SDoH and how these impact practice. RESULTS: Analyses of the literature for the realist synthesis resulted in semi-predictable patterns where outcomes could be linked to activities through mechanisms. Key mechanisms were 1) willingness to share power, 2) bridging trust and relationships 3) inter-professional knowledge support and 4) family/ community empowerment. Key features of RICHER SPPs included trust, equity and partnerships, leading to parental and community engagement, improved access to services and enriched environments. There was a measured 'critical difference' in vulnerability on the HELP Early Developmental Index (EDI) during the study period. An approach to integrating and evaluating ACEs in different SPP practice settings has been initiated through research and QI projects. CONCLUSION: Our realist synthesis identified processes of care that were effective in improving health and developmental outcomes for children and youth with adverse social and material circumstances. 'RICHER' SPPs, distributed in neighbourhood spaces, link primary and specialist care for vulnerable children and youth, improve health and developmental outcomes and foster equitable access to health care and transition services. These approaches may be translated into other contexts to improve access for more socially vulnerable children and youth and better integrate our knowledge of ACES into paediatric and youth health practices.